An analysis of the current situation of the long-term care system in Spain: Disability, precariousness, and gender - Matey, María Isabel; Martínez López, Rosa; Murillo García, Encarnación (Cuadernos de Trabajo Social, 2025)
Long-term care has become a growing concern in ageing societies, particularly in European and other rich countries. Spain launched and developed the System for Personal Autonomy and Care of Dependent Adults (SAAD) with the purpose to address that need, but the model has proven insufficient to meet the demand for long-term care. This article shows to what extent the shortcomings of the system have a detrimental impact on gender equality on the labor market, affecting a sector, the care-related jobs, characterized by low wages and poor working conditions.